Effectiveness of individualized approach for physiotherapie of chronic shoulder pain and physical functioning in elite athletes with physical disabilities - Eremiev, M.; Krumov, B.; Lyudmilova, I.; Popova, N.; Lubenova, D. (Journal of Applied Sports Sciences, 2020)
Objective: To study the potential effectiveness of individual physiotherapy program for wheelchair athletes with shoulder girdle persistent pain and dysfunctions.Materials and methods: Thirteen athletes, members of the Bulgarian National Teams in wheelchair basketball and track and field athletics, with mean age 40.6 ±10.9 participated in the study. The studied athletes had had a history of persistent pain and shoulder girdle dysfunctions for more than 6 months. Individual physiotherapy programs were applied to the participants for a period of two weeks. The selection of techniques was based on the initial assessment and evaluation. The participants were evaluated before treatment, after the first week of treatment, and at the end of the period with the use of the following specific questionnaires and tests: Goniometry of shoulder fl exion and horizontal adduction, Apley`s Scratch test, Active compression test of O`Brien (ACT), Athletic shoulder outcome rating scale and Wheelchair User`s Shoulder Pain Index (WUSPI). Results: Posttreatment effects demonstrated a signifi cant (p<.05) increase in shoulder fl exion (14.6° for the right and 12.7° for the left) and horizontal adduction (21.9° for the right and 18.8° for the left). A corresponding increase in the scores for the Athletic shoulder outcome rating scale was found with 10.92 points difference to the initial score (p<.05). The WUS-PI demonstrated a nonsignificant improvement of 0.69 points. The results of ACT and Apley scratch test showed a nonsignificant decrease of 23.1% for the right shoulder and, 15.4% decrease for the left shoulder after 7 days of treatment. Those results remained unchanged in post-treatment testing. Conclusion:This study showed that the individual physiotherapy programs are effective in the management of wheelchair athletes with chronic shoulder pain. The involvement of Mulligan`s manual therapy techniques combined with other types of exercises for the shoulder and the trunk are beneficial for wheelchair athletes with chronic shoulder pain.